Odontogenic Cervicofacial Necrotizing Fasciitis: Microbiological Characterization and Management of Four Clinical Cases - Sebastian Böttger; Silke Zechel-Gran; Daniel Schmermund; Philipp Streckbein; Jan-Falco Wilbrand; Michael Knitschke; Jörn Pons-Kühnemann; Torsten Hain; Markus Weigel; Can Imirzalioglu; Hans-Peter Howaldt; Eugen Domann; et al. (Pathogens, 2022)
Necrotizing fasciitis of the head and neck is a rare, very severe disease, which, in most cases, originates from odontogenic infections and frequently ends with the death of the patient. Rapid surgical intervention in combination with a preferably pathogen-specific antibiotic therapy can ensure patients’ survival. The question arises concerning which pathogens are causative for the necrotizing course of odontogenic inflammations. Experimental 16S-rRNA gene analysis with next-generation sequencing and bioinformatics was used to identify the microbiome of patients treated with an odontogenic necrotizing infection and compared to the result of the routine culture. Three of four patients survived the severe infection, and one patient died due to septic multiorgan failure. Microbiome determination revealed findings comparable to typical odontogenic abscesses. A specific pathogen which could be causative for the necrotizing course could not be identified. Early diagnosis and rapid surgical intervention and a preferably pathogen-specific antibiotic therapy, also covering the anaerobic spectrum of odontogenic infections, are the treatments of choice. The 16S-rRNA gene analysis detected significantly more bacteria than conventional methods; therefore, molecular methods should become a part of routine diagnostics in medical microbiology.